2003
DOI: 10.1128/aac.47.8.2507-2512.2003
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antibacterial Activity of S-3578, a New Broad-Spectrum Cephalosporin: Methicillin-Resistant Staphylococcus aureus and Pseudomonas aeruginosa Experimental Infection Models

Abstract: The in vivo antibacterial activity of S-3578, a new parental cephalosporin, was compared with those of cefepime, ceftriaxone, ceftazidime, imipenem-cilastatin, and vancomycin. The efficacy of S-3578 against systemic infections caused by methicillin-resistant Staphylococcus aureus (MRSA) SR3637 (50% effective dose [ED 50 ], 7.21 mg/kg of body weight) was almost the same as that of vancomycin. In contrast, cefepime and imipenemcilastatin were less active against this pathogen (ED 50 s, >100 and >100 mg/kg, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The left leg of each mouse was cleansed with povidone iodine and rinsed with 70% ethanol before surgical implantation of an S. aureus-coated or uninfected control pin, according to the methods previously described by Li et al (28). For antimicrobial efficacy experiments, mice were treated via subcutaneous (s.c.) injection of 50 mg of vancomycin/kg twice daily for 10 days beginning on day 14 postimplantation, which is approximately 10-fold higher than that used in previous studies (9,24,45). All other mice did not undergo any additional treatments after surgery until sacrifice.…”
Section: Methodsmentioning
confidence: 86%
“…The left leg of each mouse was cleansed with povidone iodine and rinsed with 70% ethanol before surgical implantation of an S. aureus-coated or uninfected control pin, according to the methods previously described by Li et al (28). For antimicrobial efficacy experiments, mice were treated via subcutaneous (s.c.) injection of 50 mg of vancomycin/kg twice daily for 10 days beginning on day 14 postimplantation, which is approximately 10-fold higher than that used in previous studies (9,24,45). All other mice did not undergo any additional treatments after surgery until sacrifice.…”
Section: Methodsmentioning
confidence: 86%
“…In addition, in patients with polymicrobial infections, Pseudomonas aeruginosa may be isolated in conjunction with MRSA (11). It has been reported that S-3578 has potent in vitro and in vivo activities not only against gram-negative bacteria but also against gram-positive bacteria, including MRSA (6,16).…”
mentioning
confidence: 99%
“…In order to find this, a model using MRSA, a major cause of nosocomial infections, which is widely used to assess antibiotic efficacy, was established. 23,43 PBS or D-LPs (DP7-C dosage of 0.1 or 2.5 mg/kg) was given by IV injection, 1 hour after MRSA challenge. Animals were sacrificed 20 hours later, and the number of the bacteria in the peritoneal lavage fluid was counted.…”
Section: In Vivo Cooperative Antibacterial Effect Of Dp7-c In Combinamentioning
confidence: 99%
“…aureus is a major cause of nosocomial infections, which is widely used to assess the antibiotic efficacy. 23,43 In vivo antibacterial experiments showed that D-LPs had potent antibacterial effect and showed significant synergistic effects with AZT, which markedly potentiate the antibacterial activity of AZT. Treatment with AZT-D-LPs showed a more positive therapeutic effect in mice than treatment with AZT-LPs or D-LPs alone (Figure 3).…”
mentioning
confidence: 99%